Migrasi simbolik wacana kuasa tubuh: menguak wacana tubuh dalam Ode untuk Leopold Von Sacher-Masoch karya Dinar Rahayu - Ida Nurul Chasanah (Masyarakat, Kebudayaan dan Politik, 2014)
The presence of Indonesian women writers with the dominant discourse of the power of body, presenting the pros and cons that would not go over. Female body is the language of women that can be poured through the writing of literary works. Helene Cixous brought the spirit of "writing the body" to motivate women authors to express himself through written discourse, which so far has been dominated by men. Cixous spirit is also promoted by Dinar Rahayu appear in the novel Ode untuk Leopold Von Sacher-Masoch. Dinar Rahayu voicing complexity of urban women's voices in this novel through several migration symbolic of the power of the female body. Migration is enriched by the presence of symbolic power in a sound body of Greek and Scandinavian mythology and Leopold voices in his work Venus in Furs. Through in-depth reading on the symbolic migration brought to the Ode untuk Leopold Von Sacher-Masoch through the voices of the characters and the particularities of naration techniques can be seen that this novel (as well as other sexist novels) is not merely a commodity that exploit sexuality pornography but rather an attempt to author urban female voices will be the "body power". This study uses content analysis method that begins with the reading of literature, heuristic and hermeneutic, and take advantage of intertextuality approach.